DIAGNOSTICS OF META-INSTABLE STATE OF SEISMICALLY ACTIVE FAULT - S. A. Bornyakov; Jin Ма; A. I. Miroshnichenko; Yanshuang Guo; D. V. Salko; F. L. Zuev (Геодинамика и тектонофизика, 2017)
Based on the results of a laboratory simulation of the seismic fault reactivation by “stick-slip” process, it was shown that the system of two blocks just before an impulse offset goes through the meta-instable dynamic state, with early and late stages of meta-instability [Ma et al., 2012]. In the first stage the offset begins in slow stationary mode with slow stresses relaxation on contact between blocks. In the second stage of the “accelerated synergies” strain rate increases and, subsequently, the deformation process through a process of self-organization came to dynamic impulse offset. The experimental results were used for interpretation of the results of spectral analysis of the deformation monitoring data. The data were held within the southern part ofLakeBaikal, where Kultuk earthquake (27.08.2008, Ms=6.1). took place. Its epicenter was located in the South end zone of the main Sayan fault. Monitoring of deformations of rocks was carried out from April to November2008 in tunnel, located at30 km from the epicenter of the earthquake. The time series data was divided into month periods and then the periods were processed by the method of spectral analysis. The results showed that before the earthquake has ordered view spectrogram, whereas in other time intervals, both before and after the earthquake such orderliness in spectrograms is missing. An ordered view spectrograms for deformation monitoring data can be interpreted as a consequence of the self-organization of deformation process in the transition of seismically active fault into meta-unstable before the Kultuk earthquake.